DIABETES INSIPIDUS DENGAN HIPOKALEMIA REFRAKTER - Achmad Rifa'i (Jurnal Ilmiah Kesehatan Media Husada, 2022)
Abstract Diabetes insipidus is a poluuria polydipsia syndrome with hyperexcretion of hypotonic urine. It is still rare in the world. Generally, diagnosed by dehydration and vasopressin test. It was reported that woman experienced with recurrent hypokalemia, the cause is unknown. After examination of collected urine and urine and plasma osmolarity, it was found that diabetes insipidus waspresent. A test was performed using intranasal desmopressin and it was proven that patient had nephrogenic diabetes insipidus. Woman, 44-years old with refractory hypokalemia and polyuria, suspected of having diabetes insipidus. The patient underwent a desmopressin test using 20mcg of intranasal desmopressin and there was no change in urine osmolarity. The patient was diagnosed with nephrogenic diabetes insipidus and received supportive treatment using NDAIDs. Keywords : diabetes insipidus; refractory hypokalemia. Abstrak Penyakit Diabetes Insipidus merupakan sindroma polyuria polidipsi dengan hiperekskresi urin yang hipotonis. Kejadiannya masih sangat jarang di dunia. Penentuan diagnosis umumnya dengan tes dehidrasi dan tes vasopressin. Dilaporkan seorang wanita dengan hipokalemia berulang, belum diketahui sebabnya. Setelah pemeriksaan urin tampung dan osmolaritas urin serta plasma diketahui adanya diabetes insipidus. Dilakukan tes menggunakan desmopressin intranasal dan terbukti bahwa pasien menderita diabetes insipidus nefrogenik. Wanita 44 tahun dengan hipokalemia refrakter dan polyuria, dicurigai diabetes insipidus. Pasien menjalani tes desmopressin menggunakan 20 mcg desmopressin intranasal dan tidak didapatkan perubahan dari osmolarita urin. Pasien didiagnosa diabetes insipidus nefrogenik dan mendapatkan pengobatan suportif menggunakan NSAID. Kata kunci: diabetes insipidus; hypokalemia refrakter.